2020
DOI: 10.3390/coatings10121246
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of NbxOy Thin Films: A Review

Abstract: Niobium oxides (NbO, NbO2, Nb2O5), being a versatile material has achieved tremendous popularity to be used in a number of applications because of its outstanding electrical, mechanical, chemical, and magnetic properties. NbxOy films possess a direct band gap within the ranges of 3.2–4.0 eV, with these films having utility in different applications which include; optical systems, stainless steel, ceramics, solar cells, electrochromic devices, capacitor dielectrics, catalysts, sensors, and architectural require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 147 publications
1
11
0
Order By: Relevance
“…On the other hand, RESET transition, i.e., breaking of CF, is observed when n ox migrate towards the bottom electrode (BE). The positive SET voltage indicates that memristor acts as an n-type intrinsic semiconductor, which is in good agreement with the experimental studies on Nb 2 O 5 -based memristor [26] [27]. It is found that the memristor persists in the LRS state even though the applied voltage reduces to zero, which shows the non-volatile memory property of the device.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, RESET transition, i.e., breaking of CF, is observed when n ox migrate towards the bottom electrode (BE). The positive SET voltage indicates that memristor acts as an n-type intrinsic semiconductor, which is in good agreement with the experimental studies on Nb 2 O 5 -based memristor [26] [27]. It is found that the memristor persists in the LRS state even though the applied voltage reduces to zero, which shows the non-volatile memory property of the device.…”
Section: Resultssupporting
confidence: 88%
“…The large standard deviation calculated for the characteristics of these devices may be attributed to the extremely high boiling point of NbOx, which the PVD deposition of this material undergoes at high temperature. This in turn implies exposure of the absorber layer to elevated temperatures, which may lead to its partial thermal degradation [42]. To sum up, although PVD is not an optimal method for NbOx deposition, a thickness of 30 nm leading to moderate efficiencies of the PSCs was confirmed as optimal for this material.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in these areas, a melting and recrystallization process is evidenced by plate-like grains and low-angle junctions. This effect is most probably caused by the lower melting temperature of Nb2O5 of 1512 °C [23]. The ZHCNYb sample also shows a heterogeneous microstructure, with grains of an average size of 6.53 ± 4.24 μm and intergranular pores.…”
Section: Microstructurementioning
confidence: 99%